2015
DOI: 10.1186/s12864-015-2313-7
|View full text |Cite
|
Sign up to set email alerts
|

What’s in your next-generation sequence data? An exploration of unmapped DNA and RNA sequence reads from the bovine reference individual

Abstract: BackgroundNext-generation sequencing projects commonly commence by aligning reads to a reference genome assembly. While improvements in alignment algorithms and computational hardware have greatly enhanced the efficiency and accuracy of alignments, a significant percentage of reads often remain unmapped.ResultsWe generated de novo assemblies of unmapped reads from the DNA and RNA sequencing of the Bos taurus reference individual and identified the closest matching sequence to each contig by alignment to the NC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 37 publications
(30 reference statements)
1
48
0
Order By: Relevance
“…However, these differences could also partially be artifacts since the bovine assembly is an early-stage draft assembly while the human assembly is essentially complete. Whitacre et al (32) predicted that 42% of bovine genes are either missing or misassembled in the UMD3.1 (32) assembly and this may have produced the domain differences that we found. Thus, we decided to classify these genes as “c” class until further information can be added in the literature and the assembly improved.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, these differences could also partially be artifacts since the bovine assembly is an early-stage draft assembly while the human assembly is essentially complete. Whitacre et al (32) predicted that 42% of bovine genes are either missing or misassembled in the UMD3.1 (32) assembly and this may have produced the domain differences that we found. Thus, we decided to classify these genes as “c” class until further information can be added in the literature and the assembly improved.…”
Section: Discussionmentioning
confidence: 64%
“…Expression of bovine TFs and TcoFs in 14 tissues was examined using RNA-seq data from the L1 Hereford cow Dominette 01449 described in Whitacre et al (32). Tissues included in the analysis were ampulla, white blood cells, cerebral cortex, endometrium, caruncular regions contralateral (car con) and ipsilateral (car ips) to the corpeus luteum, gallbladder, heart, jejunum, kidney, liver, mesenteric lymph nodes, pons, semitendinosus muscle, and spleen.…”
Section: Methodsmentioning
confidence: 99%
“…Our study and [23] demonstrated that it is possible to consider NGS datasets as source of metagenomics information. We could envisage that routine mining of NGS data against viral genome sequences might become a common method to discover novel viral infections and novel viruses in the future.…”
Section: Discussionmentioning
confidence: 72%
“…through ; Whitacre et al . ) were mapped without discarding the discordantly mapped reads using as reference sequences both the previously described BACs and UMD 3.1.1. Concordantly and discordantly mapped reads within the region of interest were filtered using samtools (Li et al .…”
Section: Methodsmentioning
confidence: 99%